PENGARUH SUPERVISI DAN DISIPLIN KERJA TERHADAP KINERJA GURU - Marjono, Ernawati & (Universitas Slamet Riyadi, 2007)
ABSTRACT The objectives of the research are to find out the significance of the effect of supervision and work-discipline partially and together to the Performance of the teacher of Elementary School in Jenawi Subdistrict of Karanganyar Regency. The population in this research is the teachers of State Elementary School of Jenawi Subdistrict, Karanganyar Regency as many as 183 teachers. The research employed 93 teachers or 50% of each number of teachers in training area who were employed to be sample of the study. The result of t test performed that: supervision variable did not contribute the significant effect to the Performance of the teacher of Elementary School in Jenawi Subdistrict of Karanganyar Regency. Meanwhile the work-discipline variable significantly affected to the Performance of the teacher of Elementary School in Jenawi Subdistrict of Karanganyar Regency. The result of the determination coefficient test performed that the output result of calculation of the determination coefficient test showed that the adjusted R square value was 0,258. It means that the free variable of supervision and work-discipline can elaborate the binding variable of to the Performance of the teacher of Elementary School in Jenawi Subdistrict of Karanganyar Regency; it is 25,8 percent and the left part, 74,2 percent is elaborated by the other variables which did not be studied by the writer, such as the leadership, motivation, compensation, the satisfaction of work, the work experience, etc. Keywords: supervision, work-discipline, performance